PENGEMBANGAN SUMBER DAYA MANUSIA MADURA PASCA SURAMADU - Kosim, Mohammad (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
Abstrac Suramadu bridge is like the dream comes true. Muderese must feel delighted since the problem of transportation is now resolved. On the other hand, the bridge arises a challenge, as Madura will be an open area with its consequences. Madurese people which have been marginalized by the nasional development agenda, seem are not ready to face a competing challenge. Therefore, the development of human resource of Madurese is urgently ruquired. Kata-kata kunci madura, suramadu bridge, education